TRANSFORMATIONAL PROCESSES IN NEW AGE OF THEATRE ARTS - Mahmoud Rashidov (Research Focus International Scientific Journal, 2025)
today, new socio-cultural processes are manifested in the theatrical art of the period of independence. Sufficient practical work is being done on the development of the industry. This article reflects on transformational processes in New Age Theatre Arts.